POLISH DOCTOR WŁADYSŁAW JABŁONOWSKI AND HIS MEDICAL OBSERVATIONS IN TURKEY: CONTRIBUTION TO THE UNDERSTANDING OF DERMATOLOGY AND PUBLIC HEALTH IN THE NINETEENTH-CENTURY OTTOMAN EMPIRE - Jerzy Król; Marianna Zygmunt; Marcin Poręba; Jakub Król (International Journal of Innovative Technologies in Social Science, 2025)
Medicine in the Polish lands in the nineteenth century developed through both the reception of western achievements and the creation of its original approaches adapted to local conditions. Political repression under the partitions forced many Polish physicians into exile where they continued their professional and scientific work contributing to the development of other countries’ medicine. One of them was Władysław Jabłonowski who after the January Uprising (1863-1864) emigrated to the Ottoman Empire and served as a military doctor in Baghdad.His series.“ Pol. Kazuistyka lekarska w Turcyi – Eng. Medical Casuistry from Turkey” published in Przegląd Lekarski (Cracow medical journal) between years: 1882 and 1886 offered a unique perspective on nineteenth-century medical practice in the Ottoman Empire and the Middle East. The writings provided valuable descriptions of dermatological diseases such as scabies, herpes zoster and leprosy. Jabłonowski also emphasized the role of cultural habits, hygiene and therapeutic limitations in those countries. Authors’ observations bridged Eastern and Western medical traditions, contributing not only to Polish medical literature but also to the broader history of medicine in a global context.